Integrated healthcare approach can curb the increasing cases of cryptococcosis in Africa. - Chibuike Ibe; Chinonyelum Annette Okoye (Public Library of Science (PLoS), 2022)
Cryptococcosis is a neglected tropical infection and a major cause of morbidity and mortality, especially in HIV-positive persons in Africa. Efforts to manage HIV infection have not had any significant impact on the fatalities due to cryptococcosis. An integrated healthcare approach that includes universal care coverage for Africans, expanded national care guidelines to include CrAg screening for vulnerable groups in all African countries, collaborative research, infection surveillance, and data sharing within Africa will mark a turnaround point.